Application of Different Algorithms to Optimal Design of Canal Sections - (:unkn) unknown (UNIV NACIONAL AUTONOMA MEXICO, 2014)
Today the increased world population and therefore the growth demand has forced the researchers to investigate better water canal networks distributing much more water while at least keeping its quality. Canal design formulas are explicitly obtained for different cross-sections considering minimum area but optimal design of canal sections considering seepage and evaporation losses are still an open area to study. In this study, two different algorithms are applied to this problem and results are compared with the one in literature. Genetic algorithm and sequential quadratic programming technique are used in optimization. Triangular, rectangular and trapezoidal cross-sections are optimized. It is seen that both algorithms are giving more accurate results than in literature.
Keywords: Design of canal section; genetic algorithm; sequential quadratic programming; seepage loss; CHANNEL CROSS-SECTION; TRAPEZOIDAL CHANNEL; IRRIGATION CANALS; OPTIMIZATION